Single-based and Population-based Metaheuristics for Solving NP-hard Problems - Almufti, Saman M.; Marqas, Ridwan B.; Othman, Pawan Sh.; Sallow, Amira Bibo (Iraqi Journal of Science, 2021)
Metaheuristic is one of the most well-known fields of research used to find optimum solutions for non-deterministic polynomial hard (NP-hard) problems, for which it is difficult to find an optimal solution in a polynomial time. This paper introduces the metaheuristic-based algorithms and their classifications and non-deterministic polynomial hard problems. It also compares the performance of two metaheuristic-based algorithms (Elephant Herding Optimization algorithm and Tabu Search) to solve the Traveling Salesman Problem (TSP), which is one of the most known non-deterministic polynomial hard problems and widely used in the performance evaluations for different metaheuristics-based optimization algorithms. The experimental results of Elephant Herding Optimization algorithm and Tabu Search for solving ten different problems from the TSPLIB95 library are compared.